2015
DOI: 10.3109/15563650.2015.1059945
|View full text |Cite
|
Sign up to set email alerts
|

Acute behavioural disturbance associated with phenibut purchased via an internet supplier

Abstract: Altered mental status was the predominant manifestation of phenibut toxicity in these cases. Clinicians to be aware of how phenibut toxicity may present as the internet has widened access to such substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 6 publications
2
55
0
1
Order By: Relevance
“…This cluster demonstrated severe toxicity – with all patients being intubated to control their symptoms. A similar presentation was described in two adult patients with confirmed phenibut ingestions . An American Poisons Centre series of 56 adult patients with phenibut poisoning reported an intubation rate of 20% .…”
Section: Discussionsupporting
confidence: 66%
“…This cluster demonstrated severe toxicity – with all patients being intubated to control their symptoms. A similar presentation was described in two adult patients with confirmed phenibut ingestions . An American Poisons Centre series of 56 adult patients with phenibut poisoning reported an intubation rate of 20% .…”
Section: Discussionsupporting
confidence: 66%
“…Our treatment approach in the inpatient setting of using baclofen to curb withdrawal described by Samokhvalov and colleagues, ~10 mg of baclofen to 1 g phenibut used daily, appears to have been useful in our case (2). However it must be emphasized that that commercially available phenibut has a wide range of purity, from ~40% reported by Downes et al, 2015 to 98%, reported by Wong et al, 2015, both by mass spectroscopy (6,7). While we were not able to verify phenibut purity in our case, and we had no blood or urine studies to confirm the amount of phenibut use, it stands to reason that baclofen ought to be initiated early in cases of suspected phenibut withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Acute phenibut intoxications have varying presentations, ranging from sedation and lethargy at “normal doses,” typically under 2 g over a period of days to 1.5 months, to agitation and delirium, with acute ingestions of 25–75 g (68). Minimally responsive states have been reported with doses as low as 3 g daily for 4 days (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations